My Beverly Hills kitchen : classic Southern cooking with a French twist - Hitz, Alex (Alfred A. Knopf, 2011)
"Alex Hitz blends the home cooking of his mother's Atlanta kitchen with lessons he learned in France to come up with food anyone can cook and we all want to eat. Hitz looked at the ideas behind plantation food and regional Junior League cookbooks as inspiration for updated Southern dishes. The twelve chapters in this book walk you through the steps for making everything from Shrimp Bisque, Red Pepper Tart, and Dorothy's Baked Cheddar Grits, to Pecan Crusted Salmon, Beef Bourguignon, and Chicken Pot Pie, to Salted Caramel Cake, Apple Pear Crumble, and Molten Chocolate Cake--in simple-to-follow instructions, and with irrepressible charm, Hitz shows you how to prepare a meal for two or twenty with tantalizing menus for every season. The food anyone can prepare, and everyone will want to eat, has never been this easy to prepare--or this comforting"--